Pre-emptive analgesia with diclofenac in combination with ketamine in patients undergoing laparoscopic cholecystectomy - Vikas Soni; Suman Gupta; Deepak Singh Gurjar; Nancy Ekka; Gargi Verma (Asian Journal of Medical Sciences, 2025)
Background: Laparoscopic cholecystectomy is a minimally invasive surgery which most often is associated with post-operative pain. Pre-emptive administration of ketamine and diclofenac in combination reduces post-operative pain.